Recontacting patients for multigene panel testing in hereditary cancer: Efficacy and insights. - Sawyer, Lindsey; Creswick, Heather; Lewandowski, Raymond; Quillin, John (Journal of Genetic Counseling, 2019)
In hereditary cancer, multigene panel testing is currently replacing older single‐gene approaches. Patients whose tests were previously uninformative could benefit from updated testing. Research suggests that patients desire to be recontacted about updated genetic testing, but few studies have tested the efficacy of recontact efforts. This study investigated the outcomes of a recontact effort in a hereditary cancer clinic and explored the impact of four different recontact letters, randomized in a 2X2 factorial design. Patients who had negative genetic testing for single genes or conditions were mailed letters inviting them to schedule an appointment to discuss updated testing. Patients were randomized to receive one of four letters and each letter emphasized different implications of updated multigene genetic testing: (a) personal medical management implications, (b) implications for family members, (c) both personal and family implications or (d) a control letter. The proportion of patients who arrived for appointments was assessed approximately 7 months after mailing along with associations with patient demographics and type of letter received. Letters were mailed to 586 patients who had initial testing between 2001 and 2015. Most patients were white (78%) and female (97%) with private insurance (65%). At 7 months, 25 patients (4.3%, 95% CI: 2.6% to 5.9%) had arrived for an appointment. Older age was significantly associated with response rate (p = .01), while type of recontact letter was not (p = .54). This study suggests that recontacting patients about updated genetic testing by mail does not yield a large response. It also suggests that personal and/or familial implications do not seem to be significant factors that determine response rate. Nevertheless, results provide meaningful information for cancer clinics about the outcomes of recontact efforts via informational letter.